Vanishing point [videorecording (Blu-Ray)] - Spencer, Norman, 1914-; Cain, Guillermo; Sarafian, Richard C.; Newman, Barry, 1938-; Jagger, Dean, 1903-1991; Little, Cleavon (20th Century Fox Home Entertainment, 2009)
Kowalski works for a car delivery service. He takes delivery of a 1970 Dodge Challenger that needs to go from Colorado to San Fransisco. Shortly after receiving the car, he takes a bet to get it there in less than 15 hours. After a few run-ins with motorcycle cops and highway patrol, they start a chase to bring him into custody. Along the way, Kowalski is guided by Supersoul who is a blind DJ with a police radio scanner.